Shell utilization and shell-shedding behaviour by the land hermit crab Coenobita spinosus. Issue 6 (2nd November 2019) - Sasazuka, Makoto; Hamasaki, Katsuyuki; Dan, Shigeki
Abstract : Gastropod shells are vital resources for hermit crabs for their growth, reproduction and survival. However, the land hermit crab Coenobita spinosus, which lives in wet and dark coastal forests, sheds its shell. In the present study, to understand this unique behaviour in terms of its ecological and evolutionary aspects, we examined shell utilization and shell-shedding behaviour by C. spinosus as well as sympatric C. brevimanus as a reference. We searched for land hermit crabs during the night on the island of Guam. The shells of the crabs were grasped with the fingers and held up in the air; then, crab behaviour (shell shed or not shed), body size of the crab, and shell length were recorded. Almost all individuals of C. brevimanus occupied shells of invasive giant African snails, and the larger crabs occupied larger shells, whereas C. spinosus occupied smaller snail shells. C. spinosus also utilized nut shells and plastic caps, which were much smaller than the snail shells. Our results suggest that niche differentiation in terms of shell use might have occurred through a shift in shell utilization by C. spinosus to smaller shell types. When the shells of the crabs were held up, a large proportion of C. spinosus individuals shed their shells, whereas almost all C. brevimanus retreated into and hid in their shells. It is known that diurnal birds prey on land hermit crabs. We hypothesize that when a bird grasps a shell of C. spinosus with its bill, the crab itself could be retained within the ground debris through the shell-shedding behaviour, thereby reducing the predation risk. Our hypotheses should be tested by elucidating the original shell use habits and predator-prey interactions of C. spinosus in populations on islands without invasive snails.